2012
DOI: 10.1007/s00246-012-0393-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Different-Sized Amplatzer Duct Occluders (I, II, and II AS) in Children Weighing Less Than 10 kg

Abstract: The transcatheter closure of patent ductus arteriosus (PDA) may cause more complications in small children. Amplatzer (St. Jude Medical, Plymouth, MN) has produces three types of devices for ductal occlusion: the Amplatzer duct occluder I (ADO I) and II (ADO II) and the recently introduced ADO II additional sizes (ADO II AS). We performed this study to determine the efficacy and complication rates in children who weigh <10 kg for the three types of devices used in our clinic. Between February 2007 and March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 18 publications
4
49
0
3
Order By: Relevance
“…[212223] The Liddy group reported an occlusion rate of 98% after 6 months. [22] In our study, we noted a lower immediate occlusion rate (85.7%), and this rate remained the same after 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…[212223] The Liddy group reported an occlusion rate of 98% after 6 months. [22] In our study, we noted a lower immediate occlusion rate (85.7%), and this rate remained the same after 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter closure procedures have been performed with high success rates both in children and adults [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Due to advances in diagnostic and therapeutic modalities diagnosis and treatment of PDA can be accomplished at a relatively early age [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
“…The ADO2 device provides a solution for the closure of small to moderate-sized PDAs in children 13,14 . We have demonstrated that percutaneous treatment with ADO2 can be realized with lower complication and residual shunt rates.…”
Section: Discussionmentioning
confidence: 99%
“…7 Estenose da artéria pulmonar esquerda ou coarctação da aorta, secundárias à protrusão do dispositivo, podem ser observadas em pequenos lactentes com canais de grande diâmetro que requerem o uso de próteses de maior tamanho. 16 Apesar de não termos manejado pacientes com essas características, eles teriam sido encaminhados a tratamento cirúrgico neste estudo. A ocorrência de pneumotórax em um paciente do grupo percutâneo pode ser considerada mais como complicação anestésica, não estando diretamente associada ao cateterismo.…”
Section: Discussionunclassified